Macular blood flow velocity in sickle cell disease: relation to red cell density. Issue 8 (August 1995) - Roy, M S; Gascon, P; Giuliani, D
Abstract : AIMS/BACKGROUND–While the retinal lesions of sickle cell retinopathy have been well documented, their pathogenesis remains unclear. The purpose of this study was (1) to compare macular blood flow velocity in patients with sickle cell disease and controls, and (2) to determine in sickle cell patients the relation between macular blood flow velocity and red blood cell density. METHODS–Macular blood flow velocity was measured in 18 patients with stable sickle cell disease and 45 normal controls using blue field entoptoscopy. Red blood cell density was determined by the phthalate ester density method. RESULTS–There were no significant differences between patients and controls for leucocyte velocity. However, in the sickle cell patients leucocyte velocity in the macular capillaries was significantly negatively associated with greater range of red blood cell density (p < 0.002 and p < 0.04 for right and left eyes, respectively). CONCLUSION–These results suggest that in sickle cell patients heterogeneity of the density of the red blood cells may slow down macular capillary blood flow.